Heat transfer coefficient, pressure drop and dry-out vapor quality of R454C. Flow boiling experiments and assessment of methods. (1st June 2022) - Arcasi, A.; Mauro, A.W.; Napoli, G.; Viscito, L.
Highlights: Flow boiling heat transfer, dry-out and pressure drop data for R454C. HTC increases with heat and mass flux and decreases with saturation temperature. Pressure drop increases with mass flux and decreases with saturation temperature. Dry-out occurrence anticipated with higher mass and heat fluxes. Heat transfer correlations modified to consider the temperature glide effect. Abstract: Flow boiling heat transfer, pressure drop and dry-out vapor quality of low-GWP non-azeotropic mixture R454C are experimentally evaluated. All tests are carried out in a smooth, horizontal, stainless-steel tube having an internal diameter of 6.0 mm, heated by DC current by means of Joule effect. The influence of the operating parameters in terms of mass flux, heat flux and saturation pressure is investigated and discussed. Both mass velocity and heat flux have a positive effect on the flow boiling heat transfer coefficient, whereas the saturation pressure negatively affect the boiling performance. Frictional pressure gradients are instead seen to increase with increasing mass velocity and reducing saturation pressure, while the onset of dry-out is anticipated for higher heat and mass fluxes and is unaffected by the variation of the bubble temperature. The assessment of predictive methods is carried-out for experimental data not belonging to stratified flow and post-dry-out heat transfer, that could not be predicted by conventional flow pattern maps. Finally, some tested flow boiling heat transfer coefficient correlations provide better results when modifying their nucleate boiling contribution by taking into account the negative effect of the temperature glide during evaporation.